KEEFEKTIFAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) BERBANTU MEDIA RODA KEBERUNTUNGAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN CANDI 01 SEMARANG - Erlinda, Yunita Hilda (Universitas Negeri Semarang, 2017)
Education obtained through the institution of one school. Education conducted in the learning process in the classroom. The success of the learning process can be seen on the achievement of learning objectives that have been set from the learning process in schools such as the implementation of learning memalui subjects namely mathematics. Based on interviews and observations stated that in the implementation process of learning math teachers still use conventional methods such as lectures, discussions, and assignments. Teachers are not using an innovative learning models and media pembelaajaran are less varied. Students less enthusiasm and less active in the following study. Students assume that math is a subject yag difficult. These circumstances make the learning outcomes in mathematics is low. Researchers applying the learning model Numbered Heads Together (NHT) media-assisted wheel of fortune in the learning process. The purpose of this study to determine the students can pass the study after obtaining the model and the media as well as knowing the difference between the learning outcomes using conventional methods and the learning model NHT assisted medai wheel of fortune. This study uses data collection techniques such as interviews, observation, documentation and testing. Data analysis technique used is normality test, homogeneity test, test complete learn and T-test.